Bible and canon : a modern historical inquiry - Zaman, Luc. (Studia Semitica Neerlandica, 2008)
Several decades ago canonical criticism came to dominate the study of the canon and even indeed all of biblical studies by its emphasis on the biblical canon's dogmatic content. An investigation of this canonical criticism brings its weak points to light: most notably the insufficient attention that is given to the canon's historical development. This new historical study begins with the earliest stages of the process of forming the canon rather than its final stages as most studies do. It shows how the canon, in essence, was already formed in the early stages of its historical development. It is essentially, synchronically, an authoritative unification of a range of traditions within the faith community, and diachronically, the guide that draws the dynamics of these traditions beyond their discontinuities to produce a continuity.